1889
DOI: 10.1002/cber.18890220271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen in der »Oxazinreihe«

Abstract: Ale s Oxazine Q bezeichnet man eine Reihe von Farbstoffen I), welche sich von dem Chromogen ableiten, das A. B e r n t h s e n a) unlangst durch Erhitzen von o -Amidophenol mit Brenzcatechin dargestellt und als 2 Phenazoxin Q bezeichnet hat.0. W i d m a n 3) fasst in seiner Abhaodlung Bzur N o m e n c l a t u r d e r V e r b i n d u n g e n , w e l c h e S t i c k s t o f f k e r n e e n t h a l t e n a d e n Begriff der B O x a z i n e c oder ~A z o x i n e~)~ noch weiter, indem er die Definition giebt: s A z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
10

Year Published

1962
1962
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 0 publications
1
33
0
10
Order By: Relevance
“…Recrystallization of the quaternary salt was from ethanol. A sharp melting point was found at 160°C, which is in agreement with the results ofKnorr (1904).O t h e r m a t e r i a l s w e r e o b t a i n e d a s f o l l o w s : hemicholinium-3 from Aldrich Chemical Co. Inc.; Milwaukee, Wisconsin; [N-Me-"Hlcholine chloride (10. l Ci/mmol) and Phase Combining System (PCS) from A m e r s h a m C o r p . , O a k v i l l e , O n t a r i o , C a n a d a : trichloroacetic acid from BDH Chemical Co., Toronto, Canada; precoated TLC sheets, cellulose #553 1 (without fluorescence indicator), 0.10-mm layer thickness, aluminum support from EM Laboratories Inc., BDH Chemical Co., Toronto, Canada; Tris-HCI and Tham from Fisher Scientific Co., Toronto, Canada: sodium thiosulphate, Mallinckrodt, St. Louis, Missouri; and choline iodide and albumin crystallized from bovine serum from Sigma Chemical Co., St. Louis, Missouri.…”
supporting
confidence: 85%
“…Recrystallization of the quaternary salt was from ethanol. A sharp melting point was found at 160°C, which is in agreement with the results ofKnorr (1904).O t h e r m a t e r i a l s w e r e o b t a i n e d a s f o l l o w s : hemicholinium-3 from Aldrich Chemical Co. Inc.; Milwaukee, Wisconsin; [N-Me-"Hlcholine chloride (10. l Ci/mmol) and Phase Combining System (PCS) from A m e r s h a m C o r p . , O a k v i l l e , O n t a r i o , C a n a d a : trichloroacetic acid from BDH Chemical Co., Toronto, Canada; precoated TLC sheets, cellulose #553 1 (without fluorescence indicator), 0.10-mm layer thickness, aluminum support from EM Laboratories Inc., BDH Chemical Co., Toronto, Canada; Tris-HCI and Tham from Fisher Scientific Co., Toronto, Canada: sodium thiosulphate, Mallinckrodt, St. Louis, Missouri; and choline iodide and albumin crystallized from bovine serum from Sigma Chemical Co., St. Louis, Missouri.…”
supporting
confidence: 85%
“…The literature describes various synthetic methods for the preparation of β-aminoalcohols, including the substitution reaction of primary and secondary amines with alkylene chlorohydrins [19][20] ; the reduction of α-hydroxyamides 21 and the opening of 1,2-epoxyalkanes by primary and secondary amines 22 . This last method was chosen because of its simplicity and the availability of starting materials.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of alkanolamides by reaction of acid chlorides and aminoalcohols does not appear to have been widely investigated, and published work (Knorr and Rossler, 1903;Brinziger and Koddebusch, 1949) has been largely concerned with reactions of aromatic acid chlorides. We have found that the acid chloride of 3-dimethylaminopropionic acid in chloroform reacts with ethanolamine to produce almost exclusively the unwanted O,N-bis-(3'-dimethylaminopropionyl)-2-aminoethanol (XXV), with a small yield of 2-aminoethyl 3-dimethylaminopropionate (XXVI).…”
Section: Alkunolumides Of Amino-acidsmentioning
confidence: 99%